Ten-Years Cardiovascular Disease Risk Assessment among Health Camp Attendees - Khatri, Pratima; Regmi, Bhawana; Sayami, Jamuna Tamrakar (Journal of Institute of Medicine Nepal, 2025)
Introduction:Cardiovascular disease burden has been increasing globally. The risk was greater in low-middle-income countries than in developed countries. The objective of the study was to assess the ten years of cardiovascular disease risk among the health camp attendees.Methods:Physiometric measurement of the 159 health camp attendees was used as data. The major variables were height, weight, systolic blood pressure, gender, and smoking. Likewise, a WHO non-laboratory-based risk chart was used to identify the cardiovascular risk among the attendees. The non-laboratory-based CVD risk chart categorized the participants into 5 risk groups: very low (